PENINGKATAN HASIL BELAJAR TENTANG BILANGAN BULAT MELALUI TAHAPAN-TAHAPAN PENYAJIAN J. BRUNER PADA SISWA KELAS IV SD KUTUKAN 5 RANDUBLATUNG BLORA (Improving Study Achievement on Integer through J. Bruner’s Presentation Steps to Students of Year IV, Kutuk - Murwatik, Murwatik (Jurnal Kreatif : Jurnal Kependidikan Dasar, 2010)
The backgroundÃ‚Â  of this research were dissatisfactory study achievement of the students of year IV, Kutukan 5 Primary School Randublatung Blora, and dissatisfactory capability of the teacher in teaching mathematic. The objective of this research was to improve studentsÃ¢â‚¬â„¢ activity and study result, and also teacherÃ¢â‚¬â„¢s capability in teaching integer by applying BrunerÃ¢â‚¬â„¢s presentation steps. The results of this research showed that the use of BrunerÃ¢â‚¬â„¢s presentation steps could improve studentsÃ¢â‚¬â„¢ activity in learning integer. The data showed that studentsÃ¢â‚¬â„¢ average score in activity improved, score 2.1 at cycle one, 2.3 at cycle two, and 2.4 at the last cycle. The second result was that the studentsÃ¢â‚¬â„¢ achievement in mathematics improved. The data for this result was the students got average score 65 at cycle one, 69 at cycle two, and 80 at the last cycle. The last result of the research was that teacherÃ¢â‚¬â„¢s capability in teaching integer also improved. In sequence he/she got score 1.4 at cycle one, 2.0 at cycle two, and 2.6 at cycle three. Keywords: studentsÃ¢â‚¬â„¢ achievement in mathematics, integer, J. BrunerÃ¢â‚¬â„¢s presentation steps Ã‚Â